2005
DOI: 10.1136/jcp.2004.025502
|View full text |Cite
|
Sign up to set email alerts
|

A practical approach to the clinical diagnosis of Ewing’s sarcoma/primitive neuroectodermal tumour and other small round cell tumours sharing EWS rearrangement using new fluorescence in situ hybridisation probes for EWSR1 on formalin fixed, paraffin wax embedded tissue

Abstract: Background: Over 90% of Ewing's sarcoma/primitive neuroectodermal tumour (ES/PNET) cases have the t(11;22) chromosomal rearrangement, which is also found in other small round cell tumours, including desmoplastic small round cell tumour (DSRCT) and clear cell sarcoma (CCS). Although this rearrangement can be analysed by fluorescence in situ hybridisation (FISH) using routinely formalin fixed, paraffin wax embedded (FFPE) tissues when fresh or frozen tissues are not available, a sensitive and convenient detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…FISH using EWSR1 break-apart probes is also a welladapted method for the routine demonstration of a EWSR1 gene locus rearrangement in formalin-fixed tissue. 7,11 Thanks to multimodal therapy associating initial chemotherapy and surgery with or without radiotherapy, the prognosis of ES/PNET has significantly improved, although it still remains relatively poor with a 5-year disease-free survival of about 60% for nonmetastatic patients at presentation. 14 According to the present study as well as two previously reported series, 7,8 superficial ES (ie, in the skin and/ or subcutis) has a better prognosis than deep-seated lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH using EWSR1 break-apart probes is also a welladapted method for the routine demonstration of a EWSR1 gene locus rearrangement in formalin-fixed tissue. 7,11 Thanks to multimodal therapy associating initial chemotherapy and surgery with or without radiotherapy, the prognosis of ES/PNET has significantly improved, although it still remains relatively poor with a 5-year disease-free survival of about 60% for nonmetastatic patients at presentation. 14 According to the present study as well as two previously reported series, 7,8 superficial ES (ie, in the skin and/ or subcutis) has a better prognosis than deep-seated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…10 This specific genetic abnormality can be routinely demonstrated by reverse transcriptase (RT)-PCR or by FISH. 10,11 The prognosis of bone and deep-seated soft tissue ES/PNET is poor despite various combinations of surgery, chemotherapy, and/or radiotherapy. In two small series, 7,8 it was suggested that superficial ES/PNET might have a more favorable prognosis.…”
mentioning
confidence: 99%
“…The method for in situ hybridization analysis with the Vysis break-apart probe has been previously reported. [12][13][14][15][16][17] Briefly, 100 nuclei from a tumor area were counted for probe signals under a fluorescence microscope at  1000 magnification. Only nonoverlapping tumor nuclei with two red and two green signals were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Another 10% of cases have a variant translocation fusing EWS to closely related EWS genes such as ERG, ETV1, EIAF, and FEV. The ability to identify tumor-specific chromosomal translocations and associated fusion gene transcripts using interphase reverse transcriptase-polymerase chain reaction (RT-PCR) (29,31,32) and FISH (26,32) can be useful. In the present case, limited paraffin-embedded material from a resected specimen was available for FISH studies, and epidural EES was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…FISH studies of the first specimen were performed on a formalin-fixed, paraffin-embedded tissue section using the Ewing's sarcoma breakpoint region 1 (EWSR1), dual-color, break-apart probe (Vysis, Downer's Grove, IL, USA), which spans the known common breakpoints in the EWS gene on chromosome 22q12, as described previously (25,26). Signals were enumerated in 100 nuclei from an invasive area of the tumor located by comparison with hematoxylin and eosin staining.…”
Section: Case Reportmentioning
confidence: 99%